Colecistectomía: Plastrón vesicular. - Sánchez Beltrán, Verónica Daniela (2019)
At present, acute cholecystitis is a disease that affects 20% - 30% of the population of Ecuador, this figure is increasing, so that in the country 80% to 85% of surgeries in hospitals are caused by vesicular lithiasis. In the development of the present medical history, the nursing and medical procedures that must be taken into consideration at the time of having a patient presenting cholecystectomy with vesicular plastron, for which it has been established that the domain will be 11, class 2, will be analyzed the same one that refers to physical injury (00246), presenting a risk of infection in the surgical wound. Before this procedure, nursing interventions (NIC) such as (5820) decrease in the anxiety of the patient and the family of the same, (6482 and 6486) those that refer to environmental management, (1400) management and control of the pain, (2210) administration of analgesic, (2314) administration of intravenous medications, (6540) control of infectious processes and (NOC) which are in correspondence with (1101) that speaks about the tissue integrity that is the skin and the mucous membranes and (1102) which is the healing process by first intention.